Green innovation research in the field of hospitality and tourism: the construct, antecedents, consequences, and future outlook - Gürlek, Mert; Koseoglu, Mehmet Ali (The Service industries journal, 2021)
Firms in the field of hospitality and tourism (H&T) have focused on the green innovation (GI) concept to handle environmental problems to generate revenue strategies and build brand awareness for stakeholders. This has created an important accumulation of knowledge in the literature. However, in the literature, there is no study investigating what the progress on GI literature is to help researchers in the theory development and practitioners to provide examples for their strategic decisions. Hence, This study investigates the progress in green innovation (GI) research in the field of hospitality and tourism (H&T). For this purpose, 74 studies published in 32 different journals were examined. Using content analysis, this paper examined three issues regarding green innovation research - the development levels and current trends in green innovation research; drivers and consequences, mediators and moderators of such research and agenda for future research.